1984
DOI: 10.1016/0014-5793(84)80742-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the primary structures of the two B800‐850‐apoproteins from wild‐type Rhodopseudomonas sphaeroides strain 2.4.1 and a carotenoidless mutant strain R26.1

Abstract: The α‐ and β‐apoproteins from the B800‐850‐complex of Rhodopseudomonas sphaeroides strain 2.4.1 have been sequenced. These results have been compared with those previously obtained with the analogous antenna apoproteins from the carotenoidless mutant R26.1 [9]. The α‐apoproteins differ at position 24, where a valine residue present in the wild‐type sequence is replaced by a phenylalanine residue in the mutant. The α‐apoproteins differ at the N‐terminus. In the wild‐type β‐apoprotein some chains have methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 12 publications
3
43
0
Order By: Relevance
“…Because there is only one copy of the B800-850-P polypeptide gene in the R. sphaeroides genome (27), it is likely that the difference between 15B and 15C is due to posttranslational events. Theiler et al (42,43) previously demonstrated heterogeneity in the amino termini of B800-850-P polypeptide; some contained amino-terminal methionine and the remainder had blocked amino-terminal threonine residues. This would be consistent with posttranslational modification of the P subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is only one copy of the B800-850-P polypeptide gene in the R. sphaeroides genome (27), it is likely that the difference between 15B and 15C is due to posttranslational events. Theiler et al (42,43) previously demonstrated heterogeneity in the amino termini of B800-850-P polypeptide; some contained amino-terminal methionine and the remainder had blocked amino-terminal threonine residues. This would be consistent with posttranslational modification of the P subunit.…”
Section: Discussionmentioning
confidence: 99%
“…tides have been sequenced, and their molecular weights are 6,809 and 5,457, respectively (41). Detergent-purified B800-850 complexes (7) contain two polypeptide subunits, B800-850-a and B800-850-P, which by amino acid sequence are 5,599 and 5,448 daltons, respectively (43). There are 6 molecules of Bchl per two pairs of polypeptide subunits while the Bchl/carotenoid ratio is 3:1 (50).…”
mentioning
confidence: 99%
“…Recently, more than ten of the antenna apoproteins from five different species of the photosynthetic bacteria have been sequenced (Brunisholz et al, 1984a(Brunisholz et al, , 1984bGogel et al, 1983;Tadros et al, 1983;Theiler et a!., 1984;Brunisholz et al, 1985). In general all the polypeptide subunits contain three distinct structural domains: a central hydrophobic core and which is flanked by rather polar N-and C-terminal regions.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal structure comprising the B800-850 spectral complex consists of two each of two small hydrophobic polypeptides, the B800-850-, and -a polypeptides (5,448 and 5,599 daltons [Da], respectively [38]), six molecules of Bchl, and three molecules of carotenoid (22). The purified B800-850 complex in R. sphaeroides was found (23) not to be associated with a third polypeptide as observed for the purified B800-850 complex from Rhodobacter capsulatus (15).…”
mentioning
confidence: 99%